Children's Literature at the Aceh Library and Archive Services (An Analysis of the Availability of Illustrated Story Book Collections) - Zulfa Tuffahati; Abdul Manan; Nurhayati Ali Hasan; Mukhtaruddin Mukhtaruddin; T. Mulkan Safri (AL Maktabah, 2024)
The importance of the availability of children's literature is currently a special concern in society, because children have the right to receive literature that is appropriate to their age and needs. The availability of children's literature in public libraries is an obligation and provides children's literature that is ready to be used to meet children's information needs. This research aims to determine the availability of picture story book collections, types of picture story books and the process of maintaining picture story book collections in the Aceh Library and Archives Service. This research uses qualitative research methods. The research instruments used were observation, interviews and documentation. The subjects in this research were 4 librarians and 4 deposit room staff who were selected using a purposive sampling technique because they could provide in-depth information needed by researchers. The research results show that the availability of picture book collections is not complete enough because the collection does not meet the five indicators of collection availability which are considered complete. The 5 indicators in question are: variety of types of collections, number of collections, update of collections, relevance of collections, and quality of collections. Of the 5 indicators, only 3 indicators are satisfactory, while the other 2 indicators still need improvement. There are 6 types of picture story book collections; classic fairy tales, educational books, stories about animals, adventure stories, friendship stories, family stories, and inspirational stories. The process of maintaining picture story books goes through 2 stages: 1.) Weeding, namely setting aside books that are damaged and unsuitable, then handing them over to the deposit room for follow-up. 2.) Fumigation, namely fumigation of the reading room to maintain the sterility and integrity of the books from pest attacks.